The impact of hermeneutics of nature on the development of universal hermeneutics - Bakaiev, Mykola (Filosofska Dumka, 2018)
The paper examines the development of hermeneutics from Plato to universal hermeneutics of Schleiermacher, Dilthey, Heidegger and then the possibility to expand universal hermeneutics with the help of Ihde’s hermeneutics. The distinction between specialized and universal hermeneutics is established: specialized hermeneutics specifies and interprets something specific, while universal hermeneutics universalizes and thus has a claim to be able to interpret everything. Philosophical hermeneutics itself is able to overcome all the limits, but at the same time continental version of philosophical hermeneutics known as hermeneutics of spirit (Geist) is narrowed only to humanitarian studies. This is the case when hermeneutics of nature is introduced on the example of material hermeneutics of Don Ihde. The research concludes that such hermeneutics of nature in limits of universal hermeneutics is able to overcome closure and universalize universal hermeneutics to those limits, under which it can truly surpass the limits between natural sciences and humanitarian studies as well as between different philosophical traditions in general.